Synthesis and biological activity evaluation of novel 3,5,7-trisubstituted pyrazolo[1,5-a]pyrimidines - Vlková, Kristýna; Padrtová, Růžena; Gucký, Tomáš; Peřina, Miroslav; Řezníčková, Eva; Kryštof, Vladimír (Bioorganic & medicinal chemistry letters, 2023)
Mutation of FLT3 protein kinase is often associated with deregulated cell proliferation in acute myeloid leukemia and the inhibition of this kinase is a potential therapeutic strategy. We report a novel series of 3,5,7-trisubstituted pyrazolo[1,5-a]pyrimidines prepared in an effort to study their biological activity particularly toward FLT3-ITD and its downstream regulators as well as toward CDK2 and CDK9. Derivative 10b was capable to strongly inhibit all kinases and its selectivity in FLT3-ITD expressing cell lines MOLM13 and MV4-11 was in line with FLT3-ITD inhibition. Further biochemical analyses and molecular docking confirmed FLT3 as a cellular target of 10b.
Keywords: nádorové buněčné linie; apoptóza; Protein Kinase Inhibitors; simulace molekulového dockingu; Pyrazolo[1,5-a]pyrimidines; fms-Like Tyrosine Kinase 3; Acute myeloid leukemia; FLT3; Antitumour activity; mutace; Leukemia, Myeloid, Acute; Cell Line, Tumor; Cell Proliferation; Pyrimidines; pyrimidiny; Molecular Docking Simulation; Mutation; Humans; akutní myeloidní leukemie; tyrosinkinasa 3 podobná fms; proliferace buněk; inhibitory proteinkinas; lidé; Apoptosis